Identificación de las causas asociadas a las fallas del flujo de información para el apoyo logístico aguas arriba de la perforación offshore en Colombia (2015)
The exchange of information has become a key collaboration across the supply chain factor. However, the lack of information systems to articulate and support procurement processes, causes delays in scheduled deliveries and cost overruns in the project plans. The identification of causes related to this issue, specifically in the case of operations on the Colombian Caribbean coast, constitutes an advance that will facilitate the development of a tool in future, studies aimed at optimizing the flow of information in logistics for offshore operations in Colombia.